THE EFFECT OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE WHATSAPP ON EMPLOYEE ENGAGEMENT AND EMPLOYEE PERFORMANCE - Dedi Iswanto; Ahadiat, Ayi; Ribhan, Ribhan (International Journal of Economics, Business, and Entrepreneurship, 2021)
Various studies were conducted to reveal two important and interesting things from employees, namely employee engagement and employee performance. This study aims to observe the effect of using WhatsApp among employees on employee engagement and employee performance. Two main variables of the Technology Acceptance Model theory, namely perceived usefulness and perceived ease of use are used as independent latent variables on employee engagement and employee performance which are the dependent variables. The respondents used in this study are 142 peoples, all of whom are the employees at state universities in Lampung. Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis are used to examine the structure model and the influence between latent variables and to test the hypothesis. The validity and reliability tests show valid and reliable results. The results show that in the use of WhatsApp, perceived ease of use is an important variable and is statistically proven to significantly affect employee engagement and employee performance. Meanwhile, the two TAM variables have also been shown to have a significant effect on employee engagement.